Phase transitions during compression of thaumasite, Ca3Si(OH)6(CO3)(SO4)·12H2O: A high-pressure synchrotron powder X-ray diffraction study. (October 2014) - Ardit, M.; Cruciani, G.; Dondi, M.; Garbarino, G. L.; Nestola, F.
Abstract: The high-pressure behaviour of the thaumasite structure was investigated using synchrotron powder X-ray diffraction, up to 19.5 GPa. Based on Rietveld refinements, thaumasite retained the roompressure P63 space group throughout the whole investigated pressure range while the pressure dependence of the refined unit-cell parameters can be cast into three different compression regimes, each corresponding to a different thaumasite phase (th-I, th-II and th-III) related by isosymmetric phase transitions. In particular, the phase transition in the 7.40–15.02 GPa P-range (i.e. from th-II to th-III) is associated with an inversion of the axial bulk moduli which, by analogy with ettringite, can be rationalized as due to a change in the relative strengths of the iono-covalent bonds along the [Ca3 Si(OH)6 (H2 O)12 ] 4+ columns parallel to the c axis vs. the O–H bonds linking the columns within the ab plane. The linear inverse relationship between the low- and high-temperature data from the literature with those collected under high-pressure conditions reveals that the same bonding regime governs the anisotropic expansion and contraction of thaumasite up to ~1.4 GPa and 400 K (HP-HT stability limits of th-I phase).